Endurance dan Power Terhadap IMT Pada Atlet Dayung Kontingen PON XX Sulawesi Selatan Masa Pandemi Covid-19 - Arinal Mulki Ahyar; Andi Wardihan Sinrang; Djohan Aras (Politeknik Negeri Jember, 2023)
Rowers need good muscular endurance to reach a certain distance in a short time, while muscular strength is necessary for each cycle to reach maximum speed to the finish line. Boddy Mass Index (BMI) and physical activity is one of the supporting factors for balance of the body. The decentralization training program is a particular training program for PON XX athlete, but was hampered due to the implementation of Large-Scale Social Restrictions of the COVID-19 pandemic. This study to analyze the improvement of muscle endurance and power of South Sulawesi rowers in preparation for participating in PON XX. A comparative analysis was performed on the progression in the values ​​of endurance and muscular strength over 3 months of training in 19 rowers. The muscle endurance was assessed by quantifying the sit-up, push-up, and half squat jump for 60 seconds, while the muscle power was assessed using a medicine ball. The results showed that the BMI value for muscle endurance scores with sit up was Sig (2-taield) 0.442, push up was Sig (2-taield) 0.442, and half squat jump was Sig (2-taield) 0.442, significance value > 0.05 means that the measurement of endurance to BMI are not related. In measuring muscle power with medicine ball was Sig (2-taield) 0.233, significance value > 0.05, it means that the muscle power measurement on BMI is not related. The conclusion of this study is that the assessment of endurance and muscle power of PON XX rowers during the COVID-19 pandemic is not related to BMI values. Keywords: Stunting, 1000 First Days of Life, Toddlers